2018
DOI: 10.2147/ceor.s180067
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness and budget impact of liraglutide in type 2 diabetes patients with elevated cardiovascular risk: a US-managed care perspective

Abstract: BackgroundThe Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcomes Results (LEADER) clinical trial demonstrated that liraglutide added to standard-of-care (SoC) therapy for type 2 diabetes (T2D) with established cardiovascular disease (CVD) or elevated cardiovascular (CV) risk was associated with lower rates of death from CVD, nonfatal myocardial infarction (MI), or nonfatal stroke than SoC alone.ObjectiveThe objective of this study was to assess the cost-effectiveness (CE) and budg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Glucagon-like peptide 1 (GLP-1) receptor agonists are an innovative class of medications for people with type 2 diabetes that enhances glucose-dependent insulin secretion, suppresses pancreatic glucagon production, slows gastric motility, and reduces body weight by increasing satiety and decreasing appetite (1,2). Importantly, treatment with a GLP-1 receptor agonist confers a low risk of hypoglycemia when given as monotherapy or in the absence of sulfonylureas or insulin (2), and recent studies have linked certain GLP-1 receptor agonist formulations with cardiovascular (3)(4)(5) and renal (3,4,6,7) benefits, as well as cost savings (8)(9)(10).…”
mentioning
confidence: 99%
“…Glucagon-like peptide 1 (GLP-1) receptor agonists are an innovative class of medications for people with type 2 diabetes that enhances glucose-dependent insulin secretion, suppresses pancreatic glucagon production, slows gastric motility, and reduces body weight by increasing satiety and decreasing appetite (1,2). Importantly, treatment with a GLP-1 receptor agonist confers a low risk of hypoglycemia when given as monotherapy or in the absence of sulfonylureas or insulin (2), and recent studies have linked certain GLP-1 receptor agonist formulations with cardiovascular (3)(4)(5) and renal (3,4,6,7) benefits, as well as cost savings (8)(9)(10).…”
mentioning
confidence: 99%
“…Over the lifetime of T2DM patients included in the analysis and with con rmed cardiovascular disease or high cardiovascular risk, liraglutide use was budget neutral and cost-effective [13].…”
Section: Discussionmentioning
confidence: 99%
“…Among the five basal insulin BIA studies, one of them was about insulin glargine biosimilar (13). The rest of BIA studies targeted GLP-1 RA (n = 4, including once-weekly semaglutide, oral semaglutide, and benaglutide) (12,14,25,27), DPP-4i (n = 3, including vildagliptin, saxagliptin, and linagliptin) (10,15,23), SGLT-2i (n = 2, both were dapagliflozin) (11,17) and metformin (n = 1) (19).…”
Section: Data Extractionmentioning
confidence: 99%
“…The majority of studies (n = 13) (10-12, 14-17, 19, 22-25, 27) restricted the target population on type 2 diabetes patients while some targeted type 1 diabetes patients (n = 2) (18,21), or type 1 and type 2 diabetes patients (n = 2) (20,26), and one study did not specify the target population (13). Six studies estimated the eligible population size based on a hypothetical health plan (20,(23)(24)(25)(26)(27), of which the assumed size varied widely ranging from 1 million to 35 million. All but one (23) of these studies reported the specific number of target population.…”
Section: Characteristics Of Literature Includedmentioning
confidence: 99%